The Impact of Artificial Intelligence on Improving the Quality of Public Facilities - Hussein, Mustafa Rasool (Journal of Legal and Political Studies, 2025)
Applications Of Artificial Intelligence In Developing Public Services, Developed countries are keen to employ artificial intelligence tools in various fields of governance and management within the framework of what is known as e-government, and what results from it in the field of public employment under the name of "smart management", which has become a basic requirement for improving methods of managing public utilities . The value of artificial intelligence appears more in the field of electronic administrative decisions, public facilities management, and the transformation of traditional management into smart management through digitization and electronic storage of documents or files. Customers can respond faster and they will feel that they are dealing with professional and innovative management Keywords: Administrative law, public Service, smart management, Artificial Intelligence
Keywords: Administrative law; public Service; smart management; Artificial Intelligence